2011
DOI: 10.1038/ncb2362
|View full text |Cite
|
Sign up to set email alerts
|

Caspase 8 inhibits programmed necrosis by processing CYLD

Abstract: CASPASE 8 initiates apoptosis downstream of TNF death receptors by undergoing autocleavage and processing the executioner CASPASE 31. However, the dominant function of CASPASE 8 is to transmit a pro-survival signal that suppresses programmed necrosis (or necroptosis) mediated by RIPK1 and RIPK32–6 during embryogenesis and hematopoiesis7–9. Suppression of necrotic cell death by CASPASE 8 requires its catalytic activity but not the autocleavage essential for apoptosis10, however, the key substrate processed by C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
393
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(403 citation statements)
references
References 33 publications
10
393
0
Order By: Relevance
“…From the cells co-expressing FKBP-RIP1 RHIM mut , FRB*-RIP3 WT , and HA-RIP3, we found that HA-RIP3 only interacted with AP21976-induced RIP1 RHIM mut -RIP3 WT complex, but not RIP1 RHIM mut -RIP3 RHIM mut complex (Figure 2g), thereby suggesting that inducible RIP1-RIP3 heterodimer could recruit another RIP3 protein and this recruitment may be required for necroptosis. Caspase-8 is known to inhibit necroptosis 19,20,31 and zVAD indeed tended to increase the cell death induced by RIP1-RIP3 complex, although the enhancement is not always statistically significant (Figures 2c, d and f). The participation of caspase-8 in RIP1-RIP3 dimer-induced cell death was supported by the data that caspase-8 can be detected in AP21967-induced RIP1-RIP3 complex (Supplementary Figure S2d).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…From the cells co-expressing FKBP-RIP1 RHIM mut , FRB*-RIP3 WT , and HA-RIP3, we found that HA-RIP3 only interacted with AP21976-induced RIP1 RHIM mut -RIP3 WT complex, but not RIP1 RHIM mut -RIP3 RHIM mut complex (Figure 2g), thereby suggesting that inducible RIP1-RIP3 heterodimer could recruit another RIP3 protein and this recruitment may be required for necroptosis. Caspase-8 is known to inhibit necroptosis 19,20,31 and zVAD indeed tended to increase the cell death induced by RIP1-RIP3 complex, although the enhancement is not always statistically significant (Figures 2c, d and f). The participation of caspase-8 in RIP1-RIP3 dimer-induced cell death was supported by the data that caspase-8 can be detected in AP21967-induced RIP1-RIP3 complex (Supplementary Figure S2d).…”
Section: Resultsmentioning
confidence: 95%
“…25,26 Caspase-8 and FADD negatively regulates necroptosis, [27][28][29][30] because RIP1, RIP3, and CYLD are potential substrates of caspase-8. [31][32][33][34] Necrosome also suppresses apoptosis but the underlying mechanism has not been described yet. Mixed-lineage kinase domain-like (MLKL) is downstream of RIP3, 35,36 and phosphorylation of MLKL is required for necroptosis.…”
mentioning
confidence: 99%
“…Deubiquitination of RIPK1 is known to be the critical process for assembly of the necroptotic complex. 62,76 Conversely, stabilization of RIPK1 polyubiquitin chain prevents necroptosis. 76 As discussed earlier, TAB2 is a polyubiquitin chain-binding protein and directly binds to TAK1.…”
Section: Tak1 As a Necroptosis Inducermentioning
confidence: 99%
“…66 Caspase 8 has also been shown to repress necrosis by processing CYLD. 67 Interestingly, caspase 8 appears to act in a proteolytically active complex with FADD and cFLIP to block RIP1-and RIP3-mediated necrosis, 65,68 with c-FLIP- 69 and FADD-70,71 deficient cells being highly sensitive to death by necrosis. This is consistent with the developmental lethality, due to cardiac failure, in FADDdeficient embryos, 72 with RIP1 deficiency rescuing the embryonic lethality associated with FADD deficiency.…”
Section: Rip1 and Rip3 As Drivers Of Necroptosismentioning
confidence: 99%